If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 100 + -1(100 + -1x) y = 100 + (100 * -1 + -1x * -1) y = 100 + (-100 + 1x) Combine like terms: 100 + -100 = 0 y = 0 + 1x y = 1x Solving y = 1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 1x
| x+(-5)=-7 | | 4c^3+8c=0 | | u*u+6u-7=0 | | u*u+6u=7 | | u*u*u+6u=7 | | 180-x+5x=460-5x+5x | | 10x+5y+0.05z=100 | | -x^3+6*x^2=-13x+42 | | 8r^2+2=114 | | x=2-1+2(4)-3(5)+23-12-12+23(2) | | x=2-1+2(4)-3(5)+23-12-1/2 | | x=2-1+2(4)-3(5)+23-12-1/3 | | x=2-1+2(4)-3(5)+23-12-1 | | x=2+24+123-56+23 | | x^2(x+5)=144 | | 50x=30(x+2) | | 5ysquared+18y+7=0 | | 5y+18y+7=0 | | x+x+1=1.10 | | x=15+3*-4 | | 3(15+3y)+2y=1 | | 2+4-6*2+2*5+6=10 | | 1.0-3.7x=-4.2x+0.3 | | 3.57x+1.61=4.71 | | 4y-3=80 | | -7+10=-20 | | x^3+10x+k=0 | | -3(5-9)v=25+7v | | -g+7g=6 | | 1=7v+3(v+3) | | 3j^2-4j=-1 | | 3x-4=zx-10 |